Enhanced Attachment and Proliferation of Fibroblasts on Anodized 316L Stainless Steel with Nano-pit Arrays. Issue 1626 (5th February 2014) - Ni, Siyu; Sun, Linlin; Ercan, Batur; Liu, Luting; Ziemer, Katherine; Webster, Thomas J.
ABSTRACT: The aim of this study was to prepare various sized nano-pits on 316 L stainless steel and examine their effects on the attachment and proliferation of fibroblasts. In this study, 316L stainless steel with tunable pit sizes (0, 25, 50, and 60 nm) were fabricated by an anodization procedure in an ethylene glycol electrolyte solution containing 5 vol.% perchloric acid. The surface morphology of 316L stainless steel were characterized by scanning electron microscopy (SEM). The nano-pit arrays on all the 316L stainless steel samples were in a regular arrangement. The surface properties of the 316L stainless steel nano-pit surface showed improved wettability properties as compared to the untreated 316L stainless steel. The nano-pit surfaces with 50 nm and 60 nm diameter were rougher at the nanoscale than other samples. The attachment and proliferation of fibroblasts were investigated for up to 3 days in culture using MTT assays. Compared to unanodized (that is, nano-smooth) and smooth surfaces, 50 and 60 nm diameter nano-pit surfaces dramatically enhanced the initial fibroblast attachment and growth up to 3 days in culture. The results reported in this study showed that the 50 and 60 nm nano-pit surfaces promoted fibroblast adhesion and proliferation by increasing the surface roughness and adsorption of fibronectin. Such nano-pit surfaces can be designed to support fibroblast growth and be important for improving the use of 316L stainless steel for various implant applications (such as for improved skin healing for amputee devices or for percutaneous implants).